2012
DOI: 10.1007/s00296-011-2336-6
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing polychondritis in childhood: three case reports, comparison with adulthood disease and literature review

Abstract: Relapsing polychondritis (RP) is a rare autoimmune systemic disease, especially in childhood. To report three new pediatric RP cases, to provide a literature review and to compare with adulthood disease, retrospective data collection from three childhood RP cases was observed in a Brazilian Pediatric Rheumatology Division. A literature review based on a MEDLINE database search was performed. Arthritis and auricular chondritis were present in our three patients. Two cases presented with early and severe laryngo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…The youngest patient in this series was 14 years old. Childhood RP has been described and its clinical presentations are similar to adult RP [13][14][15]. A family history of autoimmune disease is often noted in these patients although they infrequently have coexistent autoimmune diseases themselves [15].…”
Section: Discussionmentioning
confidence: 97%
“…The youngest patient in this series was 14 years old. Childhood RP has been described and its clinical presentations are similar to adult RP [13][14][15]. A family history of autoimmune disease is often noted in these patients although they infrequently have coexistent autoimmune diseases themselves [15].…”
Section: Discussionmentioning
confidence: 97%
“…With lower respiratory tract involvement, mortality in RP increases to nearly 50%. Literature review found increased utilization of tracheostomy in pediatric patients with respiratory involvement [2]. Respiratory chondritis (nasal or laryngotracheobronchial) is often asymptomatic earlier in disease.…”
Section: Discussionmentioning
confidence: 99%
“…While the auricle (83%) is classically affected most commonly in adults, the larynx and trachea (50%), nasal, costal cartilage, joints, eye (20-60%), skin (36%), and heart (<%10) are other anatomical structures that can be affected (4). Joints (36%), auricles (27%), and airway (25%) are more commonly affected in children (9). Although the pathogenesis of RP remains uncertain, the response that emerges with the deterioration of the immune balance and the association with HLA-DR4 are believed to be at least partially responsible (5).…”
Section: Discussionmentioning
confidence: 99%